Design of low noice amplifier and variable gain amplifier - Thant Zaw Oo. (2008)
CMOS Low Noise Amplifier (LNA) designs for audio frequency range and Variable Gain Amplifier (VGA) design for receiver section of ultrasound system are described in this dissertation. All simulations are performed using AMIS 0.6)im CMOS process with a 5V supply voltage. The noise performances of two different types of LNA designs and the gain performances of VGA design are simulated using ORCAD PSpice version (9.1). Primary emphasis is placed on obtaining an optimum channel length for the input pair transistors of the LNA designs in the noise optimization.